Beyond behaviour: rethinking integration for people experiencing homelessness. (9th February 2021) - Gaboardi, Marta; Santinello, Massimo; Shinn, Marybeth
Abstract: Integration is one of the main goals of homeless services. Despite the growing research on integration and homelessness, few studies start with the perspective of people experiencing homelessness. Integration is often measured as participation in a list of standard behaviours. This process assesses behaviour in accordance with social norms but ignores people's own feelings and understanding of integration. The main aim of this study is to explore the meaning of integration from the perspective of people experiencing homelessness. Data were collected through semi‐structured interviews involving 26 people in homeless service programmes. Five main themes regarding the meanings of integration were generated: work, housing, respectful relationships, family and personal dignity. Moreover, two themes of obstacles and facilitators affecting integration were identified. A new conceptualisation of integration is generated that captures the participants' sense of personal dignity, respect and recognition from others and a sense of utility within their living environments (work, house and family). Implications of the results are discussed with respect to homeless services and research on homelessness.